Salicylic acid at beans germination against salt stress - Lima, Julliane Destro de; Dedino, Diego Baraldi; Guedes, Alexandre Teixeira; Rosa, Flavio Lucas da; Lima, Gustavo Oliveira; Lima, Nastassja Kimberlly; Pinheiro, Cassia Renata; Silva, Glacy Jaqueline da (Scientia Agraria Paranaensis, 2019)
The common bean (Phaseolus vulgaris L.) is an important legume that is part of the daily food of the brazilians, being important for other countries. Because it is widely cultivated in almost all brasilian regions, is subject to environmental inclemencies, such as saline stress. Salicylic acid (S.A.) is an important plant hormone known to participate in pathways of systemic acquired resistance (SAR) against pathogens and also reported as a participant in the response to abiotic stresses. This study aimed to evaluate the action of salicylic acid prior to saline stress from three different concentrations of sodium chloride at the germination of a Brazilian common bean, cultivar Avaluna. The experiment was designed in randomized blocks, setting a 2x4 factorial scheme, with eight replicates of 25 seeds each. The following variables were evaluated: percentage of germination, root and shoot length, fresh root and shoot mass. The data were submitted to Tukey test with significance of 5%. The results indicated that there was statistically significant difference in the treatments in relation to the use of AS, that presented stable germination indexes for all evaluated treatments. This result was different from that observed in the treatments with water, where the increase of NaCl concentration resulted in a significant decrease in the percentage of germination. The results also indicated that, for the concentrations of NaCl and S.A. used in the cultivar Avaluna in this experiment, S.A. did not act as a protector against salt stress during the plant growth and development stage evaluated.